Scripting cultures : architectural design and programming - Burry, Mark (AD primer series ;, 2011)
With scripting, computer programming becomes integral to the digital design process. It provides unique opportunities for innovation, enabling the designer to customise the software around their own predilections and modes of working. It liberates the designer by automating many routine aspects and repetitive activities of the design process, freeing-up the designer to spend more time on design thinking. Software that is modified through scripting offers a range of speculations that are not possible using the software only as the manufacturers intended it to be used. There are also significant.